Cost-Effective Management of Electricity Transmission in an Industrial Region - Baev, Igor Aleksandrovich; Solovyeva, Irina Aleksandrovna; Dzyuba, Anatoliy Petrovich (Economy of Regions, 2018)
One of the worldwide modern instruments to increase power efficiency is the price-dependent electricity consumption. It is one of the elements in managing the demand for power consumption. The programs of price-dependent power consumption are globally relevant. However, in Russia, their development is still on a conceptual phase. This paper analyses regional tariffs for the power transmission from the perspective of encouraging consumers to price-dependent demand management for electricity consumption. We examine the structure of final electricity tariffs for various categories of consumers as well as identify the percentage rate for the electricity transmission for each category. We consider the methodology of single-part and two-part tariffs for electricity transmission, their structure, and advantages of application. On the example of Volga Federal District tariffs, we have calculated single-part and two-part tariffs for the power transmission in industrial enterprises in terms of three typical schedules of electricity consumption. To compare the efficiency of the price-dependent demand management for the electricity transmission in different regions of Russia, we have introduced the indicators “coefficient of the transmission tariff” and “integral coefficient of the transmission tariff”. Furthermore, we made calculations for 65 regions of Russia entering the price zones of power wholesale market. As a result of the analysis, we divided Russian regions of Russia according to the indicator of “integrated coefficient of transmission tariff” in 3 administrative groups. For each group, we have developed recommendations on price-dependent demand management for power transmission. The theoretical significance of the research consists in the development of methods for the analysis and selection of the most appropriate industrial enterprise tariff for electricity transmission. In practice, regional authorities can use the developed groups of regions to change the structure of regional tariffs in order to stimulate consumers to price-dependent power consumption. Moreover, the algorithm for calculating tariffs for electricity transmission can be applied by the industrial Russia enterprises in price-dependent demand management of power consumption to choose an optimum tariff and reduce costs on power transmission.